Application of artificial neural networks to investigate the energy performance of household refrigerator-freezers - Saidur, Rahman; Masjuki, Haji Hassan (Asian Network for Scientific Information, 2008)
In this study, the energy consumption of 149 domestic refrigerators has been monitored in Malaysian households. A questionnaire was used to get relevant information regarding the usage of this appliance in the actual kitchen environment to feed into neural networks. Prediction performance of Artificial Neural Networks (ANN) approach was investigated using actual monitored and survey data. Statistical analyses in terms of fraction of variance R2, Coefficient of Variation (COV), RMS are calculated to judge the performance of NN model. It has been found that the regression coefficient R2 is very close to unity for the best prediction performance results.